The effect of attribute framing on consumers' attitudes and intentions toward food: A meta-analysis - Irina Dolgopolova; Bingqing Li; Helena Pirhonen; Jutta Roosen (Bio-based and Applied Economics (BAE), 2021)
This paper analyzes the existing literature on the effect of attribute framing on consumers' attitudes and intentions with regard to food products. Attribute framing includes a broader interpretation of gains and losses when a product attribute is presented in a dichotomous way, such as fat vs. lean or harm vs. benefit. Meta-analysis results for the whole sample indicate that product attributes framed as gains have a higher effect on attitudes and intentions than product attributes framed as losses. Grouping studies by outcome variables, the meta-analysis demonstrates a larger effect size for studies that assess consumer attitude while for studies dealing with consumer intention, the effect size is close to zero and insignificant. We observe from the meta-regression results that the gain frame, the use of interaction terms, a specific product, and a student sample significantly influence consumers' attitudes and intentions.
Keywords: D91; I12; 330; attribute framing; food products; meta-analysis